IBN ZAID’S OPINIONS IN AL-TAWHID SHARH AL-JAMI AL-SAHIH BY IBN AL-MULAQIN FROM SURAT AL-BAQARAH TO SURAT AL-NISA, A COMPARATIVE STUDY - Moza Sa’id Abdullah Sallwma Al-Kutubi -; Asst. Prof. Dr. Mahdi Qais Abdul-Kareem - (مجلة جامعة الأنبار للعلوم الإسلامية, 2022)
This research aims to introduce Imam Abdul Rahman bin Zaid bin Aslam Al-Adawi (d.: 182 AH), and collect his sayings in interpretation, study, and balance them, from Surat Al-Baqarah to the end of Surat Al-Nisa, which was mentioned by Imam Siraj Al-Din Abi Hafs Omar bin Ali Al-Ansari, known as (Ibn al-Mulaqin) who died in 804 AH in his book al-Tawhid Sharh al-Jami al-Sahih. This study showed the great scientific status of Ibn Zayd, "may God have mercy on him", and the importance of his sayings - which are considered from the interpretation of the maxim - and we studied those sayings and compared them with the sayings of exegesis scholars; To find out the points of agreement and differences between them. In this study, we answered important questions, including Who is Imam Ibn Zayd? And what are his sayings in the interpretation and sciences of the Qur’an that Ibn al-Mulaqin mentioned in his book al-Tawhid? Did the scholars agree or disagree with these statements? The study concluded that Ibn Zayd’s sayings are of great scientific importance to scholars; We may say it in their books, and they have cited it, and some of them agreed with it and some of them disagreed with it.